Scripture re-envisioned : Christophanic exegesis and the making of a Christian Bible - Bucur, Bogdan Gabriel, (The Bible in Ancient Christianity, 2019)
Scripture Re-envisioned discusses the christological exegesis of biblical theophanies and argues its crucial importance for the appropriation of the Hebrew Bible as the Christian Old Testament. The Emmaus episode in Luke 24 and its history of interpretation serve as the methodological and hermeneutical prolegomenon to the early Christian exegesis of theophanies. Subsequent chapters discuss the reception history of Genesis 18; Exodus 3 and 33; Psalm 98/99 and 131/132; Isaiah 6; Habakkuk 3:2 (LXX); Daniel 3 and 7. Bucur shows that the earliest, most widespread and enduring reading of these biblical texts, namely their interpretation as \'christophanies\'- manifestations of the Logos-to-be-incarnate-constitutes a robust and versatile exegetical tradition, which lent itself to doctrinal reflection, apologetics, polemics, liturgical anamnesis and doxology